Cuidados de enfermería para pacientes de cardiología intervencionista: revisión sistemática - Cordero Morón, Francelis Vanessa (2025)
Patients preparation stage who undergo an interventional cardiology procedure requires achieving psycho-clinical stability to optimize their overall well-being. Objective: To analyze nursing care in the context of surgical interventions for cardiac patients based on a systematic review. Materials and Methods: This work is qualitative, descriptive, cross-sectional, and exploratory. It also employed the inductive and synthetic analytical methods, grounded in the PRISMA methodology. Results: Interventional cardiology is increasingly utilized, necessitating the training of nursing staff to ensure the success of the interventional process, patient safety, and mastery of catheterization by the paramedical team. This study considered research by other authors from different countries, and according to the reviewed literature, there is scientific evidence on various updated interventional care techniques for cardiology patients. Twenty articles were analyzed, demonstrating other procedures in patients, allowing better participation of the nursing team in patient care. Conclusions: The importance of nursing staff in the care of these patients is highlighted, showing that updated techniques can improve their participation and patient safety. Postoperative follow-up is crucial to managing complications such as arrhythmias and bleeding, and the ability of staff to identify and communicate adverse events is important, however, non-compliance can increase risks.